Religions in practice an approach to the anthropology of religion - Bowen, John Richard 1951- (Pearson, 2004)
A textbook for a course in anthropology or comparative religion looking at how people engage in the broad range of activities that invoke realities and powers beyond the reach of ordinary sense. The third edition incorporates topics that have come to the fore after 9- 11, more material on modern witchcraft, and other changes.